1994
DOI: 10.1103/physrevlett.72.4074
|View full text |Cite
|
Sign up to set email alerts
|

Clear signatures of specific inelastic and transfer channels in the distribution of fusion barriers

Abstract: Pusion excitation functions for Sm + 0 and 0 have been measured to high precision.The extracted fusion barrier distributions show a double-peaked structure which is interpreted in terms of coupling to inelastic excitations of the target. The effect of the neutron stripping channel is evident in the reaction with O. These barrier distributions show clearly the signatures of specific inelastic and transfer channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 10 publications
(13 reference statements)
2
104
0
Order By: Relevance
“…Other modes of vibrations can also be studied with this technique. In particular, the coupling to low-lying 2 + states associated to collective quadrupole vibrations are known to affect near-barrier fusion [4,31]. However, the low-lying 2 + states of 40 Ca are not found to be collective and the quadrupole strength is essentially located in the giant quadrupole resonance (GQR).…”
Section: Tdhf and CC Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other modes of vibrations can also be studied with this technique. In particular, the coupling to low-lying 2 + states associated to collective quadrupole vibrations are known to affect near-barrier fusion [4,31]. However, the low-lying 2 + states of 40 Ca are not found to be collective and the quadrupole strength is essentially located in the giant quadrupole resonance (GQR).…”
Section: Tdhf and CC Calculationsmentioning
confidence: 99%
“…In particular, couplings to rotational states [3], as well as to low-lying collective vibrations [2,[4][5][6], can enhance sub-barrier fusion by orders of magnitude as compared to a single barrier penetration model. Indeed, the couplings to collective states induce a dynamical change of the density and thus different potential barriers can be present in the entrance channel.…”
Section: Introductionmentioning
confidence: 99%
“…This is done by taking two HF ground states for the reaction and putting them in the same calculation box. In this work all frozen HF calculations were made in a box size 67.2 × 22.4 × (2 × 11.2) fm 3 in the x − y − z orientation (z = 0 is a plane of symmetry) where the collision axis is the x−axis. The maximum distance between the centres of masses was 44.8 fm.…”
Section: Numerical Detailsmentioning
confidence: 99%
“…Effects of internal nuclear structure on heavy-ion fusion can be seen by studying features of experimental fusion barrier distributions [1,2]. Experiments have shown that dynamic effects such as low-lying vibrational couplings [3][4][5] and transfer reactions [6][7][8][9][10] strongly affect fusion reactions. Other dynamic effects, such as breakup [11][12][13][14] and rotational couplings [4], have also been seen to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the fusion reactions between the strongly-bound as well as weakly-bound nuclei have been enriched due to the continuous efforts devoted by nuclear community in the field of theory [1][2][3][4][5][6][7][8][9][10] and experiments [11][12][13][14][15]. The knowledge of the mechanism of heavyion fusion reaction is very crucial to explore the nucleusnucleus potential as well as for the synthesis of super heavy elements.…”
Section: Introductionmentioning
confidence: 99%